MODELING OF WASTE WATER TREATMENT IN VERTICAL SETTLER - Petrenko, V. D.; Netesa, M. I.; Tiutkin, O. L.; Gromova, O. V.; Kozachyna, V. A. (Science and Transport Progress, 2019)
Purpose. Increasing the effectiveness of water treatment plants is an urgent technical problem. To obtain the efficiency analysis of certain facility of water treatment plant, at the design stage, it is necessary to have special mathematical models. In the paper, the development of mathematical models for assessing the performance of vertical settler having additional structural elements and used in wastewater treatment systems is considered. Methodology. The pollutant distribution in the settler has been computed using the hydrodynamics equation for the viscous incompressible fluid. Additional equation is the equation for the spread of contaminants in a vertical settler. The equations used to calculate the vertical settler take into account the most significant physical factors affecting efficiency of the settler. For numerical integration of the modeling impurity transfer equation in the water treatment plant, difference splitting schemes are used. The numerical solution of the equation describing the process of pollutant movement in a vertical settler is based on splitting this equation into the equation of a more simplified structure. For numerical integration of the modeling equations of the inviscid fluid flow, implicit difference splitting schemes are used. Numerical calculation is performed on a rectangular difference grid. Findings. On the basis of the developed numerical models, a package of application programs was created. This package allows quick determining the settler efficiency using a computational experiment. The results of a computational experiment to determine the efficiency of the settler with two plates are presented. Originality. The developed mathematical models make it possible to determine the velocity field and the impurity transfer process, taking into account the geometric shape of the settler and the use of plates, which affect the flow hydrodynamics in the water treatment plant, and therefore the efficiency of water treatment. Practical value. The calculation time for one version of the task based on the constructed mathematical models is several seconds. The models can be used to obtain an expert assessment of the operation of water treatment plants that are being designed.